Validation of an interferon-gamma enzyme-linked immunosorbent spot assay to evaluate cell-mediated immunity against severe acute respiratory syndrome coronavirus 2 - Yunhwa Kim; Eun-Jeong Jang; Ji-Young Hwang; Kyung-Min Lee; Sivilay Xayaheuang; Seok-Tae Choi; Hosun Park (Human Vaccines & Immunotherapeutics)
The COVID-19 pandemic forced the rapid development of methods to measure humoral and cellular immunity against SARS-CoV-2. The lack of a global standardized protocol and the high variability of intra- and inter-assay precision of the T-cell response made it difficult to compare T-cell assay results with those of other laboratories. The interferon-gamma enzyme-linked immunosorbent spot (IFN-γ ELISpot) assay for immunogenicity evaluation was validated using naturally infected donor peripheral blood mononuclear cells, a commercially available IFN-γ ELISpot kit, and a SARS-CoV-2 specific peptide pool. Depending on anti-CD3 and peptide pool stimulation, the mean coefficients of variation (CVs) of the intra-assay precision were 19.0% and 13.4%, respectively. The mean CVs of the inter-assay precision were 26.1% and 25.4%, and the mean CVs for reproducibility were 6.7% and 15.9%, respectively. Linearity with an R-squared value between 0.98 and 0.99 was established, and the mean CVs between the lots were 17.6% and 6.6%, depending on the anti-CD3 and peptide pool stimulation, respectively. The limit of detection was 11 spot-forming counts per well. Taken together, we demonstrated that the IFN-γ ELISpot assay is feasible for evaluating SARS-CoV-2-specific cell-mediated immune function through validation based on standard operating procedures.